2022
DOI: 10.1136/annrheumdis-2022-eular.1224
|View full text |Cite
|
Sign up to set email alerts
|

Pos0140 predicting Outcomes in Systemic Sclerosis: Stratification by Auto-Antibodies Outperforms Cutaneous Subsetting in the Eustar Cohort

Abstract: BackgroundRisk-stratification is key in a heterogeneous disease like systemic sclerosis (SSc). Until now, SSc patients are stratified according to the extent of skin involvement into limited cutaneous, diffuse cutaneous and sine scleroderma subtypes. However, this classification remains inaccurate to capture disease heterogeneity. Autoantibodies are found in more than 90% of the patients and can be detected before onset of the disease. Among them, three predominant and specific antibodies are used: anti-centro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Even in patients without skin fibrosis, the assessment of other dermatological features, such as skin telangiectasias, is of utmost importance, as such nonfibrotic manifestations were also associated with visceral manifestations, such as diastolic dysfunction. Acknowledging the specific prognosis and phenotype of ssSSc is among the necessary steps toward precision medicine and updated classification for SSc, and the term systemic sclerosis should be systematically preferred to scleroderma when designating this systemic autoimmune disease to reflect the risk of organ involvement even in patients without skin fibrosis, ie, sine (without) scleroderma …”
Section: Discussionmentioning
confidence: 99%
“…Even in patients without skin fibrosis, the assessment of other dermatological features, such as skin telangiectasias, is of utmost importance, as such nonfibrotic manifestations were also associated with visceral manifestations, such as diastolic dysfunction. Acknowledging the specific prognosis and phenotype of ssSSc is among the necessary steps toward precision medicine and updated classification for SSc, and the term systemic sclerosis should be systematically preferred to scleroderma when designating this systemic autoimmune disease to reflect the risk of organ involvement even in patients without skin fibrosis, ie, sine (without) scleroderma …”
Section: Discussionmentioning
confidence: 99%
“…The development of cellular therapies such as CAAR-T or vaccine-based immunization should also foster current initiatives to characterize the key autoantigens involved in the pathogenesis [26 ▪▪ ], with a specific focus on the pathogenic effects of autoantibodies [30]. Building on classifications derived from clinical phenotypes and prediction of clinical trajectory based on individual patients’ autoantigen and/or autoantibody profile [64,65], cellular therapies targeting the same autoantigen or related autoreactive cells may represent an unprecedented opportunity to implement personalized medicine in SSc [19].…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors associated with the presence of ILD in patients with SSc include the presence of the diffuse cutaneous form of SSc compared with limited cutaneous SSc, 4,11,12 Afro-Caribbean ethnicity, 13 male gender, [14][15][16] low values of forced vital capacity (FVC) 6 and diffusion capacity of the lung for carbon monoxide (DLCO), 14 and the presence of anti-Scl-70/ anti-topoisomerase I antibodies 11,12 as opposed to anticentromere antibodies which are more commonly linked to the development of pulmonary hypertension. Interestingly, in the large EUSTAR cohort, the autoantibody-only model outperformed the cutaneous-only sub-setting for risk-stratifying people with SSc, 12 similar to an earlier study from the same cohort. 11 In other words, the antibody status is more relevant than the limited or diffuse phenotype of cutaneous involvement to inform the risk of ILD in patients with SSc (AUC: 0.76 [0.75-0.77] vs. 0.71 [0.70-0.72]).…”
Section: Risk Factorsmentioning
confidence: 99%
“…For example, antitopoisomerase I (anti-Scl-70) antibodies have been strongly correlated with an increased prevalence and severity of ILD in SSc, offering prospects for the screening and monitoring of ILD in these patients. 6,11,12 In addition, the study of anticentromere antibodies has demonstrated their usefulness in identifying patients less likely to develop severe ILD, suggesting a potential role in the prognosis of the disease. These findings highlight the diversity of clinical presentations of SSc and the need for personalized approaches to the management of ILD, based on patients' antibody profiles.…”
Section: Serological Profile and Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation